Effects of single and combined applications of entomopathogenic fungi and nematodes against Rhynchophorus ferrugineus (Olivier) - Waqas Wakil (Nature Portfolio, 2017)
Abstract This study was carried out to investigate the insecticidal properties of Beauveria bassiana, Metarhizium anisopliae and Heterorhabditis bacteriophora for their virulence against different larval instars of Rhynchophorus ferrugineus (Olivier). Both fungi were either applied alone or in combination, with H. bacteriophora simultaneously or 1 and 2 weeks after fungal application; EPN were also applied alone. Moreover, assessment of host development, diet consumption, frass production and weight gain were observed at sub-lethal dose rates. In combined treatments, additive and synergistic interactions were observed. Synergism was observed more frequently in H. bacteriophora + B. bassiana combinations than in H. bacteriophora + M. anisopliae combinations, and was higher in early instars than old instars. In 2nd and 4th instars, synergy was noted in H. bacteriophora + B. bassiana combinations at 0, 7 and 14 d intervals and in 6th instar synergy was observed only in H. bacteriophora + B. bassiana combinations (at 0 and 7 d intervals). A decrease in pupation, adult emergence and egg hatching was enhanced in the combined treatments. Furthermore, reduced weights and variation in duration of insect developmental stages were observed among entomopathogens and enhanced in H. bacteriophora + B. bassiana combinations. Larvae treated with sub-lethal concentrations exhibited reductions in food consumption, growth and frass production and weight gain.